Carrying capacity and food self-sufficiency of paddy field resources: NDVI analysis in Batang Regency, Central Java Province, Indonesia - Ananto Aji; Edy Trihatmoko; Sigit Bayhu Iryanthony (Publisher of Widyagama University of Malang (UWG Press), 2021)
Food self-sufficiency policy in Indonesia relies on the sustainability of productive land that meets the requirements for carrying capacity of agricultural land. But the fact is that in various regions, the existence of agricultural land resources is increasingly being degraded in terms of quantity and quality. This study aims to evaluate paddy field with NDVI analysis with extensive GIS calculations and integrated with the food self-sufficiency formulas. Monitoring of paddy field area using remote sensing and mapping techniques has been well recognized and efficient. The research was conducted in Batang Regency, Central Java Province, Indonesia, that annually produces 104,211ton rice on average. The results showed that the production of lowland rice is sufficient to meet the daily rice needs of 897.19 gr per capita. The regency also showed a surplus of rice production of more than 342 gr per capita above the daily needs, fulfilling the criteria of food self-sufficiency. Food self-sufficiency classification is associated with the carrying capacity analysis found ca. 4.179 (α>1), revealing that rice production can fulfil the needs of the population of Batang Regency. JEL Classification 013; Q00; R11